(3MQcGJ GdchGcH GdSjGQI hJOHjQgGs - (3EHQGgje Hf jMji GdJLjHj GdfbGT, CHh ESMGb GdeYQha HGHf GdoqRrQbGndI,J (B493 (3g` s
(3ChdgG (B:s
(3GYde Cfg deG cGf (B( (3Gdadc (B) (3CQaY GdeMShSGJ TCfkG , hChSYgG ecGfkG , hCYXegG Ydi GdMhGOK SdWGfkG , UGQ ef GdhGLH Cf jHGOQ Edi GdHMK Yf CMhGd GdchGcH GdSjGQI Yf age cJGH GdJOHjQ s
(3BNQgG (B:s
(3hSGOS HQehOg Chd fjSGf , hSGOS HTfS Chd CjGQ , hSGHY HDhfg Chd MRjQGf , hSGHY CHjH Chd JehR , hKGef eTJQi Chd BH , hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdCNjQs
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd hCTcGds
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B79 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B128s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B693 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B862 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs